SOCIALIZATION AND COUNSELING OF SAVING MOVEMENT FOR THE EARLY YOUNG GENERATION: SOSIALISASI DAN PENYULUHAN GERAKAN MENABUNG SEJAK DINI BAGI GENERASI MUDA - Dewi Surani; Anggun Tri Prabawati; Tantri Fernanda (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
Savings and investment is one of the indicators in the country's economy that can determine the rate of economic growth. Saving money today is important. Saving money has started to be instilled early by some parents to their children. Because savings have an important role to play in the future. By instilling saving to children early, it is expected to be able to regenerate the habit of saving in the younger generation of this devotion to conduct socialization activities about saving movement to students of madrasah diniyah awaliyah in kp. Sidilem village telaga luhur, district waringin kurung, district serang-banten. This activity aims to provide knowledge and understanding about financial literacy through saving, to foster interest in saving early so that children are used to saving,as well as by giving examples of how to decorate apiggy bank with origami paper. This activity is carried out face-to-face (on the spot training) using the method of delivering socialization materials with counseling techniques, questions and answers, quizzes, piggy bank creations, as well as by adding games. Children's activities result in increasing knowledge about benefits and tips and knowing the making of piggy banks from simple materials. The socialization activities were carried out enthusiastically, as evidenced by their communicative in terms of question and answer during the event. This activity is expected to be continued by the school and also in the surrounding community and able to regenerate saving habits in the next generation of Indonesian youth who are ultimately able to contribute to the nation and the country